Rubber coating lithium battery diaphragm and preparation method thereof
By using a rubber-coated separator composed of hydrogenated nitrile rubber, polyacrylonitrile and polyimide in lithium-ion batteries, the performance degradation caused by the dissolution of transition metal cations in lithium-ion batteries is solved, and ions are captured and improved efficiently Diaphragm performance, extend battery life and improve safety.
Patent Information
- Application Number
- CN202411106749.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-13
AI Technical Summary
The dissolution of transition metal cations in the positive electrode active material in lithium-ion batteries leads to deterioration of battery performance, and existing separators are difficult to effectively capture these ions, affecting the service life and safety of the battery.
The rubber-coated lithium battery separator consisting of hydrogenated nitrile rubber (HNBR), polyacrylonitrile and polyimide (PI) is prepared by specific extraction and dehydration treatment methods to form high adhesion, temperature resistance and Good pore structure of the separator to capture transition metal ions.
It realizes efficient capture of transition metal ions, extends the battery life, improves the breathability and thermal stability of the diaphragm, and enhances the safety and performance of the battery.
Smart Images

Figure CN119171004A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery separators, and in particular relates to a rubber-coated lithium battery separator and a preparation method thereof. Background Art
[0002] Lithium battery separators are an important component of lithium-ion batteries and have a significant impact on the safety and performance of the entire battery. At present, the pace of domestic production has accelerated, and there have been significant achievements in lithium battery separators. The market share and production capacity are among the best in the world. Therefore, in order to further increase the localization rate of the high-end market, it is still necessary to increase the research efforts on lithium battery separators. The separator plays two main roles in lithium-ion batteries. First, the separator material needs to have good insulation and a certain strength to avoid direct contact between the positive and negative electrodes in the battery, and can effectively prevent short circuits caused by punctures such as burrs and dendrites, and ensure that there is no significant dimensional change under sudden high temperature conditions, thereby ensuring the safety of the battery. Second, the porous structure of the separator can provide a good migration channel for lithium ions, ensuring stable and efficient operation of the battery.
[0003] One of the main performance degradation mechanisms of lithium-ion batteries is caused by the dissolution of transition metal (especially manganese) cations in the positive electrode active material. These ions will migrate and deposit on the negative electrode surface. The deposited manganese substances (transition metals) will cause catalytic decomposition of solvent molecules and simultaneous consumption of electrochemically active lithium, leading to surface film growth, gassing, graphite particle exfoliation and overall degradation of battery performance. The ability to capture transition metal ions and enhance the service life of the battery is a very important performance of lithium battery separators, so it is of great significance to develop separators with high safety and ion capture function. Summary of the invention
[0004] In view of the deficiencies in the prior art, an object of the present invention is to provide a rubber-coated lithium battery separator.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned rubber-coated lithium battery separator.
[0006] Another object of the present invention is to provide a rubber coating slurry.
[0007] Another object of the present invention is to provide a method for preparing the rubber coating slurry.
[0008] The purpose of the present invention is achieved through the following technical solutions.
[0009] A rubber-coated lithium battery separator comprises: a base film and a coating coated on the base film, wherein the coating is obtained by coating a rubber coating slurry, wherein the coating comprises: hydrogenated nitrile rubber (HNBR), polyacrylonitrile and polyimide (PI), and the ratio of hydrogenated nitrile rubber (HNBR), polyacrylonitrile and polyimide (PI) is (0.5-10):(1-8):(6-12) by mass.
[0010] In the above technical solution, the ratio of hydrogenated nitrile rubber (HNBR), polyacrylonitrile and polyimide (PI) is preferably (1.8-2.2): (2.6-3.5): (8-11.5) by mass.
[0011] In the above technical solution, the ratio of hydrogenated nitrile rubber (HNBR), polyacrylonitrile and polyimide (PI) is preferably 2: (1.8-5): (4-20), more preferably 2: (2-4): (4-18), and more preferably 2: (2-4): (8-15) by weight.
[0012] The preparation method of the above-mentioned rubber-coated lithium battery diaphragm includes: coating the rubber-coated slurry on the base film to obtain a rubber-coated lithium battery diaphragm precursor, extracting the rubber-coated lithium battery diaphragm precursor, dehydrating it, and obtaining the rubber-coated lithium battery diaphragm.
[0013] In the above technical solution, the extraction uses an extraction liquid, and the rubber-coated lithium battery diaphragm precursor is sequentially subjected to extraction liquids with extractant concentrations from high to low, and the extractant is N-methylpyrrolidone (NMP).
[0014] In the above technical scheme, the extracting liquids with the highest to lowest extracting agent concentrations are the first extracting liquid, the second extracting liquid, the third extracting liquid and the fourth extracting liquid, respectively. The first extracting liquid, the second extracting liquid and the third extracting liquid are mixtures of extracting agent and water, and the fourth extracting liquid is water. The concentration of the extracting agent in the first extracting liquid is 65-80wt%, the concentration of the extracting agent in the second extracting liquid is 40-60wt%, and the concentration of the extracting agent in the third extracting liquid is 20-40wt%.
[0015] In the above technical solution, the dehydration treatment is drying at 50-60°C for 6-12 minutes.
[0016] A rubber coating slurry comprises hydrogenated nitrile rubber (HNBR), polyacrylonitrile and polyimide (PI). In the rubber coating slurry, the ratio of hydrogenated nitrile rubber (HNBR), polyacrylonitrile and polyimide (PI) is (0.5-10): (1-8): (6-12) by weight.
[0017] In the above technical solution, the rubber coating slurry further includes a solvent, and the solvent is a single-component solvent and / or a multi-component solvent, wherein:
[0018] The single component solvent is N-methylpyrrolidone;
[0019] The multi-component solvent includes solvent 1 and solvent 2, wherein solvent 1 is a mixture of one or more of tetrahydrofuran, methyl isobutyl ketone, and dimethylformamide, and solvent 2 is a mixture of one or two of dimethyl sulfoxide and acetonitrile.
[0020] A method for preparing a rubber coating slurry comprises: mixing a first solution, a second solution and a third solution until they are uniform to obtain the rubber coating slurry, wherein the first solution comprises: hydrogenated nitrile rubber (HNBR) and a first solvent, the second solution comprises: polyacrylonitrile and a second solvent, the third solution comprises: polyimide (PI) and a third solvent, the ratio of hydrogenated nitrile rubber (HNBR), polyacrylonitrile and polyimide (PI) is (0.5-10) : (1-8) : (6-12) by weight, the ratio of hydrogenated nitrile rubber (HNBR) to the first solvent is (5-15) : (85-95) by weight, and the ratio of the first solvent, the second solvent and the third solvent is (5-25) : (15-45) : (30-80) by weight.
[0021] In the above technical solution, the first solvent is one or a mixture of several of N-methylpyrrolidone (NMP), tetrahydrofuran, methyl isobutyl ketone and dimethylformamide.
[0022] In the above technical solution, the second solvent is one or a mixture of N-methylpyrrolidone (NMP), tetrahydrofuran, methyl isobutyl ketone and dimethylformamide.
[0023] In the above technical solution, the third solvent is one or a mixture of N-methylpyrrolidone (NMP), dimethyl sulfoxide (DMSO) and acetonitrile.
[0024] In the above technical solution, the first solvent, the second solvent and the third solvent may be the same or different.
[0025] In the above technical solution, the ratio of hydrogenated nitrile rubber (HNBR) to the first solvent is (5-15):(85-95) by mass.
[0026] In the above technical solution, the first solution, the second solution and the third solution are mixed and stirred at a stirring speed of 300 to 500 r / min for 0.5 to 2 hours until they are uniform.
[0027] In the above technical solution, the method for preparing the first solution is: dissolving hydrogenated nitrile rubber (HNBR) in a first solvent to obtain the first solution.
[0028] In the method for preparing the first solution, the method for dissolving hydrogenated nitrile rubber (HNBR) in the first solvent is: stirring at 30-45° C. and 350-400 r / min for 12-16 hours.
[0029] In the above technical solution, the method for preparing the second solution is: dissolving polyacrylonitrile in the second solvent to obtain the second solution.
[0030] In the method for preparing the second solution, the method for dissolving polyacrylonitrile in the second solvent is: stirring at 30-45° C. and 350-400 r / min for 3-5 hours.
[0031] In the above technical scheme, the method for preparing the third solution is: in a nitrogen or inert gas atmosphere, the first part of the third solvent and the diamine are mixed until uniform, and then the dianhydride and the second part of the third solvent are added in sequence, and the polycondensation reaction is carried out at room temperature and under stirring conditions for 20 to 26 hours to generate polyimide acid, and toluene is added, and the imidization reaction is carried out at 160 to 195° C. and under stirring conditions for 8 to 16 hours, and the third solution is obtained by cooling to room temperature, wherein the third solvent is composed of the first part of the third solvent and the second part of the third solvent, and the ratio of the third solvent, diamine, dianhydride and toluene is (200 to 250): (11 to 15): (33 to 36): (21 to 26) by mass.
[0032] In the method for preparing the third solution, the ratio of the first part of the third solvent to the second part of the third solvent is (80-150):(100-200) by mass.
[0033] In the method for preparing the third solution, the diamine is 4,4'-diaminodiphenyl ether, and the dianhydride is 4,4'-bisphenol A type diether dianhydride.
[0034] In the above technical solution, the organic solvent needs to be dehydrated before use, and the organic solvent is any one of the first solvent, the second solvent and the third solvent.
[0035] In the above technical solution, the water removal method is: drying the molecular sieve at 150°C to 230°C for 2 to 4 hours, adding the dried molecular sieve to the organic solvent and standing for 2 to 6 hours, and the ratio of the dried molecular sieve to the organic solvent is (85 to 92): (8 to 15) by mass.
[0036] Application of rubber coated lithium battery separator in lithium-ion battery.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] 1. HNBR is introduced into the rubber coating slurry of the present invention, so that the rubber coating lithium battery diaphragm has higher bonding force; PI is introduced to make the rubber coating lithium battery diaphragm have higher temperature resistance; the present invention also innovatively introduces polyacrylonitrile, and the good compatibility of polyacrylonitrile and HNBR brings uniformly distributed pores to the diaphragm. It is the first time to find that polyacrylonitrile has dense and uniformly distributed pore-forming function in the oil-based coating diaphragm, which improves the air permeability of the diaphragm;
[0039] 2. The rubber-coated lithium battery separator of the present invention has a good transition metal ion capture effect;
[0040] 3. The present invention has high repeatability and is easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the SEM of the diaphragm prepared in Example 5;
[0042] Figure 2 This is the SEM of the separator prepared in Comparative Example 5. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0044] The purchase sources of the drugs involved in the following embodiments and comparative examples are as follows:
[0045] Hydrogenated nitrile rubber (HNBR), purity 99.5%;
[0046] Polyacrylonitrile (powder), purity 99.9%, molecular weight 200,000;
[0047] N-methylpyrrolidone (NMP), purity 99.5%;
[0048] 4,4'-diaminodiphenyl ether, purity 99%;
[0049] 4,4'-Bisphenol A diether dianhydride, purity 98%;
[0050] Toluene, purity 99.5%
[0051] Positive electrode sheet (ternary positive electrode, ternary material is LiN i0.8 Co 0.2 O2);
[0052] Negative electrode sheet (graphite negative electrode).
[0053] The models and manufacturers of the equipment involved in the following embodiments and comparative examples are as follows:
[0054] Scanning electron microscope, Sigma 300, Carl Zeiss, Germany;
[0055] Japan AsahiSeiko Asahi Seiko air permeability meter, model EH01-551MR;
[0056] Japan Shimadzu stretching machine, model, AGS-X (100N);
[0057] Electrochemical workstation, CHI660E, Shanghai Chenhua Instrument Co., Ltd.;
[0058] Withstand voltage insulation analyzer, AN9636HS, Qingdao Ainuo Intelligent Instrument Co., Ltd.;
[0059] In the following examples, the first solvent, the second solvent and the third solvent all need to be dehydrated before use.
[0060] The method for removing water from the first solvent is: drying the molecular sieve at 200°C for 3 hours, adding the dried molecular sieve to the first solvent, and standing for 4 hours. The ratio of the molecular sieve to the first solvent is 90:10 by mass, and the molecular sieve is a hydrated aluminosilicate.
[0061] The method for removing water from the second solvent and the third solvent is the same as the method for removing water from the first solvent.
[0062] In the following examples, the base film is a polyethylene film having a thickness of 9 μm.
[0063] Diaphragm adhesion test method: Cut the diaphragm into a shape of 25 mm × 60 mm, use tape to stick on the diaphragm, and use a Shimadzu stretching machine to tear the tape and the diaphragm apart. The force used is the diaphragm adhesion. The diaphragm is one of the diaphragms prepared in Examples 5 to 8 and Comparative Examples 5 to 8.
[0064] Battery pole piece bonding force test method: Cut the diaphragm into a shape of 25mm×150mm, cut the battery pole piece into a shape of 25mm×60mm, stack the diaphragm and the battery pole piece together, use a battery pole piece press to hot press, the hot pressing pressure is 1000KG, the hot pressing temperature is 80℃, the hot pressing time is 1s, use a Japanese Shimadzu stretching machine to tear the battery pole piece and the diaphragm apart, the force used is the battery pole piece bonding force, wherein the battery pole piece is a positive pole piece (the obtained battery pole piece bonding force is the positive pole bonding force) or a negative pole piece (the obtained battery pole piece bonding force is the negative pole bonding force). The diaphragm is one of the diaphragms prepared in Examples 5 to 8 and Comparative Examples 5 to 8.
[0065] Embodiments 1 to 4
[0066] A method for preparing a rubber coating slurry comprises: mixing a first solution, a second solution and a third solution, stirring at a stirring speed of 400 r / min for 1 hour until uniform, to obtain a rubber coating slurry, wherein the first solution is a mixture of hydrogenated nitrile rubber (HNBR) and a first solvent, the second solution is a mixture of polyacrylonitrile and a second solvent, the third solution comprises: polyimide (PI) and a third solvent, the ratio of hydrogenated nitrile rubber (HNBR), polyacrylonitrile and polyimide (PI) is X by weight, the ratio of hydrogenated nitrile rubber (HNBR) to the first solvent is 10:90 by weight, the first solvent is N-methylpyrrolidone (NMP), the second solvent is N-methylpyrrolidone (NMP), the third solvent is N-methylpyrrolidone (NMP), and the ratio of the first solvent, the second solvent and the third solvent is Y by weight. The values of X and Y are shown in Table 1.
[0067] The method for preparing the first solution (hydrogenated nitrile rubber solution) is: mixing granular hydrogenated nitrile rubber (HNBR) and a first solvent, stirring at 35° C. and 380 r / min for 14 hours to dissolve the hydrogenated nitrile rubber (HNBR) in the first solvent, and obtaining a first solution.
[0068] The method for preparing the second solution (polyacrylonitrile solution) is as follows: powdered polyacrylonitrile and a second solvent are mixed, and stirred at 35° C. and 380 r / min for 4 h to dissolve the polyacrylonitrile in the second solvent to obtain a second solution.
[0069] The method for preparing the third solution is: in a nitrogen atmosphere, mixing the first part of the third solvent and the diamine, stirring for 10 minutes until uniform, then adding the dianhydride and the second part of the third solvent in sequence, and performing polycondensation reaction at room temperature and stirring for 24 hours to obtain polyimide acid, adding toluene, and performing imidization reaction at 180° C. and stirring for 9 hours, cooling to room temperature, and obtaining the third solution, wherein the first part of the third solvent and the second part of the third solvent constitute the third solvent, and the ratio of the third solvent, diamine, dianhydride and toluene is 210:13.6356:35.4373:24.7 by mass, and the ratio of the first part of the third solvent to the second part of the third solvent is 100:126 by mass, the diamine is 4,4'-diaminodiphenyl ether, and the dianhydride is 4,4'-bisphenol A type diether dianhydride.
[0070] Table 1
[0071] Example X Y Example 1 2:3:10 18:27:66.9 Example 2 1:3:12 9:27:79.3 Example 3 2:2:12 18:18:79.3 Example 4 2.5:4.5:6 22.5:40.5:33.15
[0072] Comparative Example 1
[0073] A method for preparing a coating slurry comprises: mixing a first solution prepared in Example 1, a solvent A and a third solution prepared in Example 1, stirring until uniform, to obtain a coating slurry, wherein the ratio of hydrogenated nitrile rubber (HNBR) in the first solution, the solvent A and the polyimide (PI) in the third solution is 1.5:30:10 by mass, and the solvent A is N-methylpyrrolidone (NMP).
[0074] Comparative Example 2
[0075] A method for preparing a coating slurry comprises: mixing a first solution prepared in Example 1, a second solution prepared in Example 1 and a solvent B, stirring until uniform, to obtain a coating slurry, wherein the ratio of hydrogenated nitrile rubber (HNBR) in the first solution, polyacrylonitrile in the second solution and the solvent B is 1.5:3:50 by weight, and the solvent B is N-methylpyrrolidone (NMP).
[0076] Comparative Example 3
[0077] A method for preparing a coating slurry comprises: mixing a C solvent, a second solution prepared in Example 1, and a third solution prepared in Example 1, and stirring until uniform to obtain a coating slurry, wherein the ratio of the C solvent, the polyacrylonitrile in the second solution, and the polyimide (PI) in the third solution is 20:2:10 by mass, and the C solvent is N-methylpyrrolidone (NMP).
[0078] Comparative Example 4
[0079] A method for preparing a coating slurry is basically the same as Example 1 "A method for preparing a rubber coating slurry", the only difference being that the first solution is different. The method for preparing the first solution (SBR solution) in this comparative example is: mixing granular styrene butadiene rubber (SBR) and a first solvent, stirring at 35°C and 380 r / min for 14 hours to dissolve the styrene butadiene rubber (SBR) in the first solvent, to obtain a first solution, wherein the ratio of styrene butadiene rubber (SBR) to the first solvent is 10:90 by mass.
[0080] Examples 5 to 8 and Comparative Examples 5 to 8
[0081] A method for preparing a diaphragm comprises coating a slurry on a base film to obtain a diaphragm precursor, extracting the diaphragm precursor (extracting NMP), and drying it in an oven at 55°C for 8 minutes for dehydration treatment to obtain a diaphragm, wherein the extraction adopts an extracting liquid, and the diaphragm precursor is sequentially subjected to extracting liquids with extractant concentrations from high to low, the extracting liquid is N-methylpyrrolidone (NMP), and the extracting liquids with extractant concentrations from high to low are sequentially a first extracting liquid, a second extracting liquid, a third extracting liquid, and a fourth extracting liquid, the first extracting liquid, the second extracting liquid, and the third extracting liquid are each a mixture of an extracting liquid and deionized water, and the fourth extracting liquid is deionized water, wherein the concentration of the extracting liquid in the first extracting liquid is 80wt%, the concentration of the extracting liquid in the second extracting liquid is 50wt%, and the concentration of the extracting liquid in the third extracting liquid is 30wt%. The slurry is one of the rubber coating slurries prepared in Examples 1 to 4 and the coating slurries prepared in Comparative Examples 1 to 4. The diaphragms (rubber coating lithium battery diaphragms) of Examples 5 to 8 are obtained in sequence from Examples 1 to 4, and the diaphragms of Comparative Examples 5 to 8 are obtained in sequence from Comparative Examples 1 to 4, as shown in Table 2.
[0082] Table 2
[0083]
[0084]
[0085] The membrane bonding strength, positive electrode bonding strength and negative electrode bonding strength of the membranes prepared in Examples 5 to 8 and Comparative Examples 5 to 8 are shown in Table 3.
[0086] Table 3
[0087]
[0088] It can be seen from Table 3 that the membrane adhesion, positive electrode adhesion and negative electrode adhesion of the diaphragm prepared by the slurry containing HNBR are much greater than those of the diaphragm prepared by the slurry containing HNBR. The performance of the diaphragm prepared by the slurry containing HNBR is higher than that of the diaphragm prepared by the slurry containing SBR. The adhesion of the diaphragm prepared by the rubber coating slurry of Example 1 reaches the maximum.
[0089] The membranes prepared in Examples 5 to 8 and Comparative Examples 5 to 8 were subjected to membrane permeability test, breakdown voltage test, thermal shrinkage test and ion conductivity test, and the permeability value, breakdown voltage, thermal shrinkage rate and ion conductivity were obtained in turn. The membrane was placed on a Japanese Asahi Seiko permeability meter and tested evenly (one point was tested every 10 cm) at 10 points, and the average value of the 10 points was taken to obtain the permeability value of the membrane; the membrane was laid flat on the test conductive plate of the withstand voltage insulation analyzer, 50 breakdown points were tested, and the average value of the 50 breakdown points was taken to obtain the breakdown voltage; the membrane was cut into 4 cm × 6 cm, and its area change in a 150°C oven for 1 hour was measured to obtain the thermal shrinkage rate (measurement of heat resistance stability); the ion conductivity was obtained by AC impedance method at room temperature and 100% RH. The test results are shown in Table 4.
[0090] Table 4
[0091]
[0092] It can be seen from Table 4 that adding polyacrylonitrile to the slurry can reduce the air permeability of the diaphragm, and the introduction of PI can effectively improve the breakdown voltage and thermal shrinkage performance of the diaphragm, making the diaphragm have more stable performance. The diaphragms prepared in Examples 5 to 8 also have good ionic conductivity.
[0093] The diaphragms prepared in Comparative Example 5 and Example 5 were subjected to microscopic scanning to obtain SEM images. Figure 2 It can be seen that no voids are formed on the diaphragm prepared by using the slurry without adding polyacrylonitrile, so the air permeability value is quite large. Figure 1 The SEM shows that the diaphragm prepared in Example 5 has more micropores, and the role of polyacrylonitrile is apparent, so polyacrylonitrile has a certain pore-forming function.
[0094] The diaphragms prepared in Example 5, Comparative Example 7 and Comparative Example 8 were tested for their capture effect of transition metal ions (the transition metal ions are iron ions, nickel ions and manganese ions). The diaphragms prepared in Example 5, Comparative Example 7 and Comparative Example 8 were cut respectively to obtain 3 cut diaphragms of the same size. The 3 diaphragms of the same example or comparative example were taken as a sample, and the content of transition metal ions in the 3 diaphragms of each sample was tested by ICP, and the average value was calculated, as shown in Table 5 "Element content before immersion".
[0095] The three cut diaphragms of each sample were immersed in an electrolyte containing 500ppm of transition metal ions for 1 day. The electrolytes containing 500ppm of transition metal ions in which the three diaphragms of each sample were immersed were: an electrolyte containing 500ppm of iron ions, an electrolyte containing 500ppm of nickel ions, and an electrolyte containing 500ppm of manganese ions. Each diaphragm was immersed in only one electrolyte. After immersion, the diaphragms were taken out and ICP tested to test the transition metal ion content in the diaphragms. The test results are shown in Table 5 "Element Content after Immersion". The electrolyte in the electrolyte was LiPF6, the concentration of the electrolyte was 1.0M, the electrolyte solvents were ethyl carbonate, methyl carbonate and dimethyl carbonate, and the volume ratio of ethyl carbonate, methyl carbonate and dimethyl carbonate was 1:1:1.
[0096] Table 5
[0097]
[0098] Through ICP testing of the diaphragm, it can be seen that hydrogenated nitrile rubber has a higher capture effect on nickel, manganese and iron ions. Compared with styrene-butadiene rubber, hydrogenated nitrile rubber has better capture ability.
[0099] By comparing Example 5 with Comparative Examples 5 to 8, the air permeability of Comparative Example 5 is very high and cannot be used; the thermal shrinkage of the diaphragm prepared in Comparative Example 6 is poor; the bonding force of the diaphragm prepared in Comparative Example 7 mainly comes from PI, and PI can only provide a relatively low bonding force, and the bonding force of Comparative Example 7 is relatively poor; compared with Comparative Example 8, the diaphragm prepared in Example 5 has a more excellent bonding force, and the air permeability is lower than that of Comparative Example 8;
[0100] The ion capture experiment further proves that the diaphragm prepared in Example 5 has excellent ion capture effect compared with that in Comparative Example 8. By comparing the example and the comparative example, the diaphragm prepared by hydrogenated nitrile rubber, polyacrylonitrile and polyimide in a preferred proportion has excellent performance. To a certain extent, the three play a synergistic role to construct a corresponding excellent lithium battery diaphragm.
[0101] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A rubber-coated lithium battery separator, characterized in that: include: A base film and a coating coated on the base film, wherein the coating comprises hydrogenated nitrile rubber, polyacrylonitrile and polyimide, and the ratio of hydrogenated nitrile rubber, polyacrylonitrile and polyimide is (0.5-10):(1-8):(6-12) by weight.
2. The method for preparing the rubber-coated lithium battery separator according to claim 1, characterized in that: include: The rubber coating slurry is coated on the base film to obtain a rubber coating lithium battery diaphragm precursor, and the rubber coating lithium battery diaphragm precursor is extracted and dehydrated to obtain a rubber coating lithium battery diaphragm.
3. The preparation method according to claim 2, characterized in that: The dehydration treatment is drying at 50-60° C. for 6-12 minutes.
4. A rubber coating slurry, characterized in that: include: The ratio of hydrogenated nitrile rubber, polyacrylonitrile and polyimide in the rubber coating slurry is (0.5-10):(1-8):(6-12) by weight.
5. The rubber coating slurry according to claim 4, characterized in that: The rubber coating slurry further comprises a solvent, which is a single-component solvent and / or a multi-component solvent, wherein: The single component solvent is N-methylpyrrolidone; The multi-component solvent includes solvent 1 and solvent 2, wherein solvent 1 is a mixture of one or more of tetrahydrofuran, methyl isobutyl ketone, and dimethylformamide, and solvent 2 is a mixture of one or two of dimethyl sulfoxide and acetonitrile.
6. A method for preparing a rubber coating slurry, characterized in that: include: The first solution, the second solution and the third solution are mixed until uniform to obtain a rubber coating slurry, wherein the first solution comprises hydrogenated nitrile rubber and a first solvent, the second solution comprises polyacrylonitrile and a second solvent, and the third solution comprises polyimide and a third solvent. The ratio of hydrogenated nitrile rubber, polyacrylonitrile and polyimide is (0.5-10):(1-8):(6-12) by weight, the ratio of hydrogenated nitrile rubber to the first solvent is (5-15):(85-95) by weight, and the ratio of the first solvent, the second solvent and the third solvent is (5-25):(15-45):(30-80) by weight.
7. The method according to claim 6, characterized in that The first solvent is one or a mixture of N-methylpyrrolidone, tetrahydrofuran, methyl isobutyl ketone and dimethylformamide.
8. The method according to claim 7, characterized in that The second solvent is one or a mixture of N-methylpyrrolidone, tetrahydrofuran, methyl isobutyl ketone and dimethylformamide.
9. The method according to claim 8, characterized in that The third solvent is one or a mixture of N-methylpyrrolidone, dimethyl sulfoxide and acetonitrile.
10. Use of the rubber-coated lithium battery separator as claimed in claim 1 in lithium-ion batteries.
Citation Information
Patent Citations
Polyacrylonitrile diaphragm coating liquid, lithium battery diaphragm and lithium battery
CN109504226A
Lithium ion battery ultrathin composite diaphragm and preparation method thereof
CN115133218A
High adhesive separator for battery comprising pvac-pma copolymer and secondary battery comprising same
CN115443579A
Hydrogenated nitrile rubber slurry as well as preparation method and application thereof
CN116606459A
Diaphragm and battery thereof
CN116995364A
Cited By
Composite coating diaphragm, preparation method thereof and lithium battery
CN121367030A
Composite coating separator, method for preparing the same and lithium battery
CN121367030B
Modified hydrogenated nitrile rubber oil-based adhesive, method for preparing the same, and use thereof
CN122706282A
